2011
DOI: 10.1088/0741-3335/53/3/035024
|View full text |Cite
|
Sign up to set email alerts
|

Local effects of ECRH on argon transport in L-mode discharges at ASDEX Upgrade

Abstract: Abstract. The transport of argon as trace impurity has been investigated in electron cyclotron resonance heated L-mode discharges at ASDEX Upgrade to test recent theories predicting the rise of an outward impurity convection. The profiles of the argon transport coefficients for r/a < 0.65 have been determined by analysing the linear flux-gradient dependency of the total argon ion density evolution after the puff. A new methodology to experimentally obtain the total impurity ion density from the integrated use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(108 citation statements)
references
References 26 publications
8
98
0
2
Order By: Relevance
“…In [53,54] it has been found that impurity accumulation occurs when turbulent transport in the plasma core is weak, and the neoclassical transport becomes important. The cleaning effect of large turbulent core transport is not only based on diffusive effects, but also supported by a turbulent outward pinch for the impurities requiring steep temperature gradients [55,56]. The radiation/heating balance in the core of the presented Pulse No: 81913 (Fig.5) reveals radiative cooling of similar size as the local heating power thereby decreasing the core T e and flattening the T e gradients leading to a feedback loop of decreasing transport and increasing radiation [49].…”
Section: W Accumulationmentioning
confidence: 77%
“…In [53,54] it has been found that impurity accumulation occurs when turbulent transport in the plasma core is weak, and the neoclassical transport becomes important. The cleaning effect of large turbulent core transport is not only based on diffusive effects, but also supported by a turbulent outward pinch for the impurities requiring steep temperature gradients [55,56]. The radiation/heating balance in the core of the presented Pulse No: 81913 (Fig.5) reveals radiative cooling of similar size as the local heating power thereby decreasing the core T e and flattening the T e gradients leading to a feedback loop of decreasing transport and increasing radiation [49].…”
Section: W Accumulationmentioning
confidence: 77%
“…In the edge of the core plasma but still on the inside of the ETB, impurity transport is dominated by plasma turbulence and diffusion coefficients have typical values of a few m 2 s −1 , while v/D values are low. This was shown by investigations on helium, neon [22], silicon [23] and argon [24]. Further out in the ETB, recent impurity transport investigations on helium, carbon, neon and argon have shown, that the radial transport in the ETB between ELMs is in accordance with collisional transport coefficients [9,8] D neo = D CL + D P S and the collisional radial drift velocity v neo is v neo = v CL + v P S .…”
Section: Impurity Transport Modelmentioning
confidence: 87%
“…Detailed transport investigations using tracer impurities show that the local heating leads to a strong increase of anomalous transport [53]. This could be further detailed in [54] where the Ar tracer transport was compared to quasi-linear gyro-kinetic simulations, which qualitatively reproduce the positive convection and its decreasing trend for radii outside the ECRH deposition radius. However, for the most central ECR-heated discharge analysed, the resulting strong positive (outward) convection is probably not of turbulent nature but could be caused by the strong MHD activity present within the q = 1 surface.…”
Section: W Transport and Contentmentioning
confidence: 94%